Risk analysis of PPP financing for toll road project - Suwandairi Y.D.; Suratkon A.; Amin M.; Tsarwan O.T.; HJ Wahyu (BIO Web of Conferences)
The Indonesian Government has limited funds to provide infrastructure facilities for its population of 261 million people, which requires an investment of US$ 6.445 trillion. Only 37% of this can be covered by government funds, necessitating the use of private funds for the remaining 63%. Public-Private Partnership (PPP) offer a solution for infrastructure development in Indonesia, where the government collaborates with the private sector to provide public infrastructure. However, PPP implementation faces challenges, such as changes in bank financial policies that affect financing schemes. The purpose of this study is to analyze the feasibility and variable risks of project funding through sensitivity analysis. A single case study approach was used to gather data. The results indicate that the Serang-Panimbang toll road project is feasible. Additionally, three parameters are identified as high risk: investment cost, income, and interest rate. The findings of this study are beneficial for the government and construction service actors involved in PPP projects. They also serve as a valuable literature review for academics studying PPPs.